Characterization of copper nanopowders after natural aging - Amelkovich Yu. A. Yuliya Alexandrovna; Nazarenko O. B. Olga Bronislavovna; Sechin A. I. Aleksandr Ivanovich; Putkhenpurakalchira M. V. Maniyan Visakkh (2015, 2015)
Title screen